Oportunidades y retos para innovaciones en las cadenas de valor de maíz y frijol en Honduras: resultados de estudio de alcance del WP2 - Reyes, Byron A.; Colindres, Mirian; Rodríguez, Carlos; Donovan, Jason A.; Peña, Carmen Meliza; Stoian, Dietmar (2022)
This presentation contains preliminary results of a scoping study conducted in Honduras in 2022 by WP2 of the Rethinking Markets Initiative, focusing on beans and maize value chains.